Unclonable Anti‐Counterfeiting Labels Based on Microlens Arrays and Luminescent Microparticles. Issue 9 (17th March 2022) - Kumar, Vinay; Dottermusch, Stephan; Katumo, Ngei; Chauhan, Aditya; Richards, Bryce S.; Howard, Ian A.
Abstract: Micron‐scale randomness during manufacturing can create unique and unclonable anti‐counterfeiting labels. The security of such labels typically comes at the expense of complex hardware being required for authentication. This work demonstrates unclonable labels that can be authenticated using simple hardware such as a standard light‐emitting diode and smartphone camera. These labels consist of a microlens array laminated to a luminescent‐microparticle‐doped polymer film, and thereby present a new method of making microscopic particle distributions visible on the macroscopic scale. The current novel design offers two significant practical advantages: 1) use of an incoherent source; and 2) authentication independent of the detector position. A comparison of 100 test images against 100 different reference images (total of 10, 000 comparisons out of which 100 should authenticate and 9900 should not), demonstrates that authentication is robust with an estimated probability of a false positive on the order of 10 −15 . Finally, a proof‐of‐concept is demonstrated through successful authentication of a label by a single smartphone, simultaneously providing both excitation and detection on the front side of the label. Abstract : An unclonable anti‐counterfeiting label based on a microlens array laminated to a microphosphor doped layer is demonstrated. Upon illumination, constellations of bright emission points are created corresponding to where a microparticle lies in the focus of a microlens. These unique patterns, and their change with angle of incidence, form the basis for an unclonable label.